An inversion inv(4)(p12–p15.3) in autistic siblings implicates the 4p GABA receptor gene cluster. Issue 5 (23rd March 2006) - Vincent, J B; Horike, SI; Choufani, S; Paterson, A D; Roberts, W; Szatmari, P; Weksberg, R; Fernandez, B; Scherer, S W
Abstract : Introduction: We describe the case of two brothers diagnosed with autism who both carry a paracentic inversion of the short arm of chromosome 4 (46, XY, inv(4)(p12–p15.3)). We have determined that this inversion is inherited from an apparently unaffected mother and unaffected maternal grandfather. Methods/Results: Using fluorescence in situ hybridisation analysis and Southern blot hybridisation we identified the breakpoints. The proximal breakpoint (4p12) maps to a region containing a cluster of gamma-aminobutyric acid A (GABA(A)) receptor genes, and directly interrupts the GABRG1 gene, the distal-most gene of the cluster. We also identified an insertion/deletion polymorphism for a ∼2 kb LINE1 (L1) element that occurs within intron 7 of GABRG1 . Our genotype analysis amongst autism families indicated that the L1 deletion allele did not show increased transmission to affected individuals. No linkage disequilibrium was evident between the L1 and single nucleotide polymorphisms in adjacent GABA(A) receptor genes on 4p, where a recent study has identified significant association with autism. Discussion: Despite this, the identification of an inversion breakpoint disrupting GABRG1 provides solid support for the genetic involvement of the short arm of chromosome 4 in the genetic aetiology of autism, and for the hypothesis of disrupted GABA neurotransmission in autism.